Characterizing the Impact of Specific Genetic Mutations on Chemotherapy Resistance and the Efficacy of Oncolytic Viruses for the Treatment of Ovarian Cancer - Cudmore, Alison (Université d'Ottawa / University of Ottawa, 2022)
Epithelial ovarian cancer (EOC) is the most lethal gynecologic cancer and urgently requires new therapies. Oncolytic viruses (OV) are a strong contender. OVs interact with immune components of the TME, which can be altered due to specific genetic mutations. The present study evaluates the impact of specific tumour mutations on the response to carboplatin, the current standard of care, and VSV∆M51, a promising OV candidate. After a study of genetically diverse models, constitutive KRas activation enhanced VSV∆M51 replication in-vitro and sensitivity in syngeneic in-vivo models. VSV∆M51 prolonged survival in syngeneic tumour- bearing mice with KRas, Trp53 and Pten mutations, including one tumour model that did not respond to carboplatin. Response to VSV∆M51 in-vivo was associated with activation of CD4+ and CD8+ T lymphocytes in the peritoneal TME. In summary, VSV∆M51-based immunotherapy has shown promise in diverse murine models of EOC bearing clinically relevant mutations.
Keywords: Ovarian Cancer; Oncolytic Virus; Immunotherapy; Tumour Mutations; Carboplatin; High Grade Serous Carcinoma; Murine Models; Tumour Microenvironment